Between ideals and reality in home-based rehabilitation - Sissel Steihaug; Jan-W. Lippestad; Anne Werner (Taylor & Francis Group, 2016)
Setting and objective The growing elderly population and the rising number of people with chronic diseases indicate an increasing need for rehabilitation. Norwegian municipalities are required by law to offer rehabilitation. The aim of this study was to investigate how rehabilitation work is perceived and carried out by first-line service providers compared with the guidelines issued by Norway's health authorities. Design and subjects In this action research project, qualitative data were collected through 24 individual interviews and seven group interviews with employees - service providers and managers - in the home-based service of two boroughs in Oslo, Norway. The data were analysed using a systematic text-condensation method. Results The results show that rehabilitation receives little attention in the boroughs and that patients are seldom rehabilitated at home. There is disagreement among professional staff as to what rehabilitation is and should be. The purchaser-provider organization, high speed of service delivery, and scarcity of resources are reported to hamper rehabilitation work. Conclusion and implications A discrepancy exists between the high level of ambitious goals of Norwegian health authorities and the possibilities that practitioners have to achieve them. This situation results in healthcare staff being squeezed by the increasing expectations and demands of the population and the promises and statutory rights coming from politicians and administrators. For the employees in the municipalities to place rehabilitation on the agenda, it is a requirement that authorities understand the clinical aspect of rehabilitation and provide the municipalities with adequate framework conditions for successful rehabilitation work.Key points Home-based rehabilitation is documented to be effective, and access to rehabilitation has been established in Norwegian law. The purchaser-provider organization, high rate of speed, and a scarcity of resources in home-based services hamper rehabilitation work. Healthcare providers find themselves squeezed between the health authorities' overarching guidelines and requirements and the possibilities of achieving them. Rehabilitation must be placed on the agenda on the condition that authorities understand the clinical aspect of rehabilitation.